IMPLEMENTASI POMPA AIR TENAGA SURYA UNTUK MENINGKATKAN KETAHANAN PANGAN DAN PENDAPATAN: KASUS KELOMPOK TANI WANITA ADELWEIS, KELOMPOK MAWA, KOTA PALOPO - Rahmawati, Hilda; Suhardi, Suhardi; Sohriati, Eva; Hijra, Hijra (Universitas Mataram, 2025)
Food security is a fundamental aspect of rural development, particularly for smallholder farming groups that rely heavily on natural resources. The Adelweis Farmer Group, consisting of ten women farmers located in Mawa Subdistrict, Sendana District, Palopo City, has long struggled with limited agricultural productivity due to reliance on manual irrigation and unfavorable market conditions. In response, a training and mentoring program was initiated to utilize Solar Power Plants (PLTS) as an alternative energy source to operate water pumps for irrigation. The initiative also included capacity building in resource management, product packaging, and marketing strategies. This study aims to evaluate the effectiveness of PLTS implementation in enhancing crop productivity, particularly water spinach (Ipomoea aquatica), and its impact on increasing farmer income. A qualitative-descriptive method was employed through field observations, in-depth interviews, and documentation. Findings revealed that the use of solar energy not only reduced operational costs but also expanded cultivated areas and increased harvesting frequency. Consequently, farmers’ income significantly improved, and agricultural product distribution became more efficient. These results highlight the critical role of integrating renewable energy technologies in small-scale agriculture as a strategy for sustainability and local food security.